Desain Mini Soil Moisture Sensor Untuk Deteksi Kekeringan Tanaman Pot - Sari, Herva Emilda; Priyono, Hary; Tumanggor, Benelekser (Universitas Multi Data Palembang, 2025)
Technological advances in today's digital era are the latest breakthroughs that are a way out of many existing problems. The community is a part that needs technological updates, which can facilitate large and small daily tasks. Like gardening tools in ancient times required a complicated process in caring for plants, but now caring for plants can be easy because of the existence of technological tools that can help care for the plants. Like the simplest thing is watering plants, if you forget it can make the plants wilt and look stale or even die. The Mini soil moisture sensor is designed to provide a warning of soil dryness in potted plants indoors. This tool provides a warning to the owner of the ornamental plant pot, that the soil in their favorite plant pot is dry. The design of the humidity detection sensor tool is used to detect a lack of water in the soil and send voltage to the LED. So that if no water is detected in the soil that is embedded in this tool, the LED will light up. The warning light from the LED on this tool is part of the Mini soil moisture sensor design to be able to provide a warning to the owner of ornamental plants about their plants. So that plants that are cared for indoors can safely get enough water from the Mini soil moisture sensor warning design.